2013
DOI: 10.1186/2193-1801-2-106
|View full text |Cite
|
Sign up to set email alerts
|

Utility of two novel multiplexing assays for the detection of gastrointestinal pathogens – a first experience

Abstract: BackgroundCause for gastroenteritis range from viral, bacterial to parasitic pathogens. Rapid Multiplexing techniques like ProGastro_SSCS and xTAG_GPP can detect broad panels of pathogens simultaneously.We performed a field test with a total number of 347 stool samples from adult hospitalized patients that were tested with the Luminex xTAG GPP assay; of the 157 samples positively tested for at least one pathogen by xTAG GPP a total number of 30 samples was retested with the ProGastro SSCS assay. Assays were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…Pathogens were tested according to the physician's request only. Two studies 19,34 considered as few as two pathogens in common with the PHE algorithm, whereas two restricted conventional testing to only five pathogens 28 and four pathogens. 30 Rand et al…”
Section: Comparatormentioning
confidence: 99%
See 4 more Smart Citations
“…Pathogens were tested according to the physician's request only. Two studies 19,34 considered as few as two pathogens in common with the PHE algorithm, whereas two restricted conventional testing to only five pathogens 28 and four pathogens. 30 Rand et al…”
Section: Comparatormentioning
confidence: 99%
“…Seven studies 19,22,26,27,29,35,39 reported the setting sufficiently to allow judgement on the origin of the infection (hospital vs. community). The majority of studies 11,12,20,21,[23][24][25]28,[30][31][32][33][34][36][37][38] reported recruitment of hospitalised patients, for which a mixed population should be assumed (in terms of origin of infection) as it is unclear at what point in time during hospitalisation each infection occurred. Only one study was identified as a community study, set in Côte d'Ivoire.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations